Green technology for sustainable urban life - Bhowmik, Abhijeet; Dahekar, Rahul M (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Human Civilization uses technology for supporting day to day activities of urban life. New technologies are more efficient and environment friendly due to increased awareness and recent development in research areas of energy management. The adoption of technology is limited and has adverse effects on environment and human civilization. Therefore, scope exists for application of new technologieswhich are more environmental friendly for supporting day to day activities of an urban lifestyle. These technologies are characterized as green or clean technology. Green technologies involve: energy efficiency, recycling, safety and health concerns, renewable resources, and many more. This paper reviews various technologies from view point of adaptability and implementation issues for modern living towards sustainable environment. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->